Pengembangan Ekowisata Mangrove Gili Sulat Sebagai Upaya Keberlanjutan Ekosistem Pesisir dan Karbon Biru (Blue Carbon) untuk Bahan Ajar Pembelajaran IPA - Listantia, Nora; Idrus, Agil Al (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
In this paper, the author wants to examine the development of the benefits of Gili Sulat mangrove ecotourism in relation to the concept of blue carbon which can be integrated into efforts to develop ecotourism on sustainable coasts and waters. This research is descriptive qualitative research. Data sources consist of primary and secondary data. Primary data collection was carried out by interviews using questionnaires, focus group discussions and observation of all activities in the Gili Sulat ecotourism area. Secondary data was obtained by searching literature and publications carried out by relevant agencies and documenting research results. Interview techniques using questionnaires were carried out to be more efficient in identifying the parameters to be analyzed and to find out the respondents' desires. The aquatic ecosystem on Gili Sulat is very beneficial for the people of Tekaloq hamlet, Sugian village as protection from disasters, such as abrasion, erosion, high waves. The link between blue carbon and ecotourism can be a strong measuring tool to support the preservation of coastal and aquatic ecosystems. Increasing public awareness about environmental conservation, ecotourism, and the role of blue carbon in mitigating climate change is very important to achieve sustainability and is a step in increasing public awareness and knowledge that can be carried out by stakeholders in collaboration with experts and environmental activists. By increasing public awareness and sustainable management efforts, it is hoped that it can support ecotourism activities which can make a significant contribution to mitigating climate change through the blue carbon concept.